Respuesta :

Ah tbh I don't know which way u want to love it but it says rewrite so idk maybe just type the same equation for it

Answer:

To complete the square move the non-x term to the right

2x^2 + 13x = -20 then divide equation by x^2 coefficient

x^2 + 6.5x = -10

then coefficient of x (which is 6.5) divide by 2 (3.25) square the number

=10.5625 Then add 10.5625 to both sides of the equation:

x^2 + 6.5x + 10.5625 = -10 + 10.5625

x^2 + 6.5x + 10.5625 = .5625

Take the square root of both sides

(x + 3.25)^2 = .75

Step-by-step explanation: